A New species of Pseudochalcura Ashmead (Chalcidoidea: Eucharitidae) from Argentina with descriptions of alternate sexes of two other species - Torrens, Javier (2016)
Pseudochalcura Ashmead is a genus of parasitic wasps within Eucharitidae (Chalcidoidea) that are all parasitoids of ants. The genus is widespread in the New World, with different species known from the Yukon and Alaska to northern Chile and Argentina. Descriptions of the adults (both sexes) of Pseudochalcura carinata sp. Nov. from Argentina, and of the males of P. pauca Heraty and P. prolata Heraty are provided. A revised identification key to species is included.